CORRELATION OF READINESS TO CHANGE, INTENTION TO QUIT AND SEVERITY OF DEPENDENCE OF TOBACCO USE AMONG THE RELATIVES OF THE PATIENTS VISITING PSYCHIATRY OPD IN A TERTIARY CARE CENTRE- A CROSS-SECTIONAL STUDY - Shoeb Khan; Gaurav Wadgaonkar; Arvind Karad; Manjeet Santre (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction- The WHO estimates that the tobacco epidemic is one of the greatest risks to global public health, killing more than 8 million people per year, including over 1.2 million fatalities from exposure to second-hand smoke. Therefore, the present study attempted to understand the pattern of tobacco use, nicotine dependence, and readiness to change behaviour among tobacco users attending a psychiatric outpatient Department. Methods & Materials- Cross-Sectional Study was conducted among the relatives of the patient attending Psychiatry OPD, which belongs to the Tertiary care Hospital, Pune. This study purposively (Non-Probability Random sampling) recruited 100 people currently using tobacco in any form in the study. Data were collected by a face-to-face interview method using the pretested, Semi-structured questionnaire having questions pertaining to sociodemographic details, nicotine dependance, Readiness to change behavior, intention to quit. Results- The total number of subjects was 100 in the study. Most patients were males (82%) and the mean age was 33.6 (±9.13) years. 14% of the participants were identified as having significant dependence. The intention to quit was higher among individuals aged 31-45 years (50%), males (88%), those with less than secondary education (61%), married individuals (75%), students and those with other occupations (59%), Hindus (79%), and those belonging to the middle socioeconomic class (54%). Conclusion- Significant Nicotine dependence levels was low, and a substantial majority expressed a strong intention to quit smoking. These results emphasize the importance of tailored interventions, especially for specific age and education groups. Furthermore, our study suggests that demographic factors may not be strongly associated with nicotine dependence